Individual strategic profiles in tacit coordination games. Issue 1 (2nd January 2021) - Mizrahi, Dor; Laufer, Ilan; Zuckerman, Inon
ABSTRACT: In tacit coordination games people manage to converge on prominent solutions, which are known as focal points. There is still no accepted explanation of how players manage to converge on the same solution. It could be that the limited explanatory power arises from the fact that existing theories rely on pure strategies to describe behaviour. The aim of the current study is to construct a cognitive model that more accurately describes human behaviour in tacit coordination games. To this end we constructed individual strategic profiles that take into account the subjective preferences of individual players regarding the prominent selection rules. Subsequently, the individual profiles were clustered to gain insights regarding different types of coordinators. By using machine learning and statistical methods we were able to demonstrate, for the first time, the relationship between different types of strategic profiles and coordination ability. The results of this study demonstrate the importance of constructing a descriptive behavioural model that may potentially improve prediction of human decision-making in the context of human-machine interaction.